Moringa oleifera seed extract: A review on its environmental applications - Idris, Munirat Abolore; Jami, Mohammed Saedi; Hammed, Ademola Monsur; Jamal, Parveen (Research India Publications, 2016)
This review focus on the use of Mornga oleifera seed extract and it application in the environment. It is usually referred to as the miracle tree because of its vast usefulness of its various parts. It is a source of protein, calcium, iron, carotenoids and phytochemicals utilized for several usage in developing countries. The plant parts have been used in various application such as medicine, cosmetics, food supplements and water purification. This review presents the various application of Moringa oleifera seed extract as an adsorbent, coagulant, dewatering agent and as a disinfectant. This review also highlight the various methods used in processing the seed extracts, different phytochemical and chemical constituents present in the seed extract. Other aspects that require further investigation were also highlighted in this review.